Montelukast deprescribing in outpatient specialty clinics: A single center cross-sectional study - David C. Foote; Jamie L. Miller; Grant H. Skrepnek; Stephen Neely; Kiya Bennett; Paul M. Boylan (Elsevier, 2024)
Objective: To identify and evaluate montelukast deprescribing in outpatient specialty clinics. Methods: This was a single-center, retrospective, cross-sectional study conducted at an academic health system in the southern US including 21 specialty clinics. Subjects included adults ≥18 years with an active prescription for montelukast who attended at least one appointment in pulmonology, otolaryngology, or neurology outpatient specialty clinics between January 1, 2021 to December 31, 2022. Patients <18 years and those with diagnoses of uncontrolled asthma or allergic rhinitis were excluded. Outcomes assessed included the frequency and period prevalence of montelukast deprescribing, defined by a documented montelukast discontinuation within the medical record, and evaluation of reasoning for discontinuation mentioned in visit notes. Results: There were 1152 patients who met inclusion criteria. Of these, 43 (3.7 %) experienced a montelukast deprescribing event: 18 (41.9 %) in neurology, 13 (30.2 %) in otolaryngology, and 12 (27.9 %) in pulmonology. Documented reasons for deprescribing were only available for 11 patients (25.6 %); reasons for deprescribing included patient-provider shared decision-making regarding the Black Box Warning [n = 5 (11.6 %)], inadequate treatment response [n = 3 (7.0 %)], suicidal thought development [n = 1 (2.3 %)], adverse drug event [n = 1 (2.3 %)], and pregnancy planning [n = 1 (2.3 %)]. Conclusion: Montelukast deprescribing rates were less than 5 % in outpatient specialty clinics. Factors associated with montelukast deprescribing beget further investigation.